Nutrition of Edible Seaweed Kappaphycus alvarezii Related to Different Environmental Coastal Water Condition - Eko Nurcahya Dewi; Darmanto Darmanto; Ambariyanto Ambariyanto (Journal Omni-Akuatika)
Edible seaweed K. alvarezii collected from different coastal waters in Indonesia (Morowali and Teluk Ekas). The seaweed was extracted into semirefined carrageenan and it was determined on their nutrition quality. The results showed that the essential amino acids content of the three different samples SRC were similar as follows: aspartic acid, glutamic acid, serine, glysine, arginine, alanine, tyrosine, methionine, valine, phenylalanine, isoleucine, leucine and lysine. The gel strength (g/cm2) and viscosities value in Morowali, Ekas coastal waters and commercial SRC were different in the samples. FTIR spectroscopy determined  that  molecular present in three samples were kappa carrageenan.